Keratinocyte growth factor-2 and autologous serum potentiate the regenerative effect of mesenchymal stem cells in cornea damage in rats - Ferda Alpaslan Pınarlı; Gülsen Ökten; Ümit Beden; Tunç Fışgın; Mehmet Kefeli; Nurten Kara; Feride Duru; Leman Tomak (International Journal of Ophthalmology, 2014)
AIM:To investigate the healing process after severe corneal epithelial damage in rats treated with mesenchymal stem cells (MSCs) cultured with or without keratinocyte growth factor (KGF-2) and autologous serum (AS) on amniotic membrane (AM). Many patients are blind and devastated by severe ocular surface diseases due to limbal stem cell deficiency. Bone marrow-derived MSCs are potential sources for cell-based tissue engineering to repair or replace the corneal tissue, having the potential to differentiate to epithelial cells.METHODS:The study included 5 groups each including 10 female “Sprague Dawley” rats in addition to 20 male rats used as bone marrow donors. Group I rats received AM+MSCs, Group II rats AM+MSCs cultured with KGF-2, Group III rats AM+MSCs cultured with KGF-2+AS, Group IV rats only AM and Group V rats, none. AS was derived from blood drawn from male rats and bone marrow was obtained from the femur and tibia bones of the same animals. Therapeutic effect was evaluated with clinical, histopathological and immunohistochemical assessment. MSC engraftment was demonstrated via detection of donor genotype (Y+) in the recipient tissue (X) with polymerase chain reaction.RESULTS:Corneal healing was significantly better in Groups I-III rats treated with MSC transplantation compared to Group IV and Group V rats with supportive treatment only. The best results were obtained in Group III rats with 90% transparency, 70% lack of neovascularization, and 100% epithelium damage limited to less than 1/4 of cornea.CONCLUSION: We suggest that culture of MSCs with KGF-2 and AS on AM is effective in corneal repair in case of irreversible damage to limbal stem cells.